Mosquitoes and potatoes: How global health crises impede development - Maurizio Malpede; Giacomo Falchetta; Soheil Shayegh (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2021)
The socioeconomic fallout of the COVID-19 pandemic has been felt globally and across many sectors and population groups. While the long-term impact of the pandemic on economic growth is yet to be observed and assessed, history may provide some evidence on how public health emergencies have negatively affected socioeconomic development pathways well beyond the crisis duration. Here we examine the impact of malaria on the contribution of potato to the Old World's development during the 18th and 19th centuries. We exploit local variations in land suitability for potato cultivation and malaria transmission to estimate and compare the impact of growing potato on urbanization and population growth in highly endemic and non-endemic areas. We show that local weather conditions ideal for malaria transmission counteracted the potential benefits of introducing the potato in the Old World. Robustness checks from geographic variations in malaria stability, suitability for potato cultivation, and placebo treatments reinforce the positive effects of eradicating malaria on urbanization and population growth in potato-suitable areas after 1900. Our results highlight the interplay between technological change, public health, and development outcomes.
Keywords: 330; Public health; Population; Urbanization; Malaria; Development